An experimental study on the low energy impact behavior of different number of layer e-glass/epoxy composites - Günöz, Alper (İdris Karagöz, 2025)
Composite materials are increasingly used in structural applications due to the high strength-to-weight ratio, corrosion resistance, and design flexibility they offer; however, susceptibility to impact damage remains a critical concern, particularly in layered configurations. In the present research, low-velocity impact experiments were performed on 8-layer and 16-layer unidirectional E-glass/epoxy composite plates with [+45/-45/90/0]s and [+45/-45/90/0]2s stacking sequences, which were manufactured using the vacuum-assisted hand lay-up method, at impact energy levels of 10, 20, and 30 J. Findings indicated that a rise in impact energy resulted in an increase in maximum contact force and energy absorption for both 8-layer and 16-layer composite plates, with no noticeable change in bending rigidity. At the same energy level, an increase in the number of layers enhanced the maximum contact force and bending rigidity of the composite plates, whereas displacement and the amount of energy absorbed by the material decreased. For all energy levels, the damage observed in the 8-layer composite plates spread over a wider area compared to the damage in the 16-layer plates.

Kompozit malzemeler, yüksek özgül dayanım, korozyon direnci ve tasarım esnekliği gibi avantajları sayesinde yapısal uygulamalarda giderek daha fazla kullanılmaktadır; ancak, özellikle tabakalı yapılarda darbe hasarına karşı duyarlılık önemli bir endişe kaynağı olmaya devam etmektedir. Bu çalışmada, vakum destekli el yatırma yöntemiyle üretilen [+45/-45/90/0]s ve [+45/-45/90/0]2s tabakalama dizilimlerine sahip 8 ve 16 tabakalı tek yönlü E-cam/epoksi kompozit plakalara 10, 20 ve 30 J’lük düşük hızlı darbe testleri uygulanmıştır. Bulgular, darbe enerjisindeki artışın hem 8 tabakalı hem de 16 tabakalı kompozit plakalar için maksimum temas kuvvetinde ve enerji absorpsiyon miktarında artışa yol açtığını, ancak eğilme rijitliğinde belirgin bir değişim meydana getirmediğini göstermiştir. Aynı darbe enerjisi seviyesinde, tabaka sayısındaki artış kompozit plakaların maksimum temas kuvvetini ve eğilme rijitliğini artırırken, deplasman ve malzeme tarafından soğurulan enerji miktarında azalmaya neden olmuştur. Tüm enerji seviyelerinde, 8 tabakalı kompozit plakalarda oluşan hasarın, 16 tabakalı plakalarda oluşan hasara göre daha geniş bir alana yayıldığı gözlemlenmiştir.
Farklı katman sayısındaki e-cam/epoksi kompozitlerin düşük enerjili darbe davranışı üzerine deneysel bir çalışma
Keywords: Solid Mechanics; Katı Mekanik [EN] Composite and Hybrid Materials; Kompozit ve Hibrit Malzemeler